PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA VIDEO ANIMASI DAN KOTAK AJAIB TERHADAP HASIL BELAJAR DI SMP NEGERI 1 LEWA TIDAHU - Julita Hamba Banju, Iin; Makaborang, Yohana; Ndjoeroemana, Yohana (Jurnal Biogenerasi, 2024)
This study aims to determine the impact of the Problem Based Learning model assisted by animated video media and the Magic Box on learning outcomes at SMP Negeri 1 Lewa Tidahu. The results of data analysis showed that the average posttest of students in the experimental class implemented using the problem based learning model assisted by animated video media and the Magic Box was 73.04 higher than the value of students in the class using the discovery learning model of 61.03. Based on the Independent Sample Test, the value indicated by sig. (2 tailed) is 0.005 and this value is less than 0.05. so it can be concluded that H0 is rejected and H1 is accepted, this shows that the Problem Based Learning learning model assisted by animated video media and the Magic Box has a positive effect on the learning outcomes of class IX students at SMP Negeri 1 Lewa Tidahu.